Comparison and Analysis of Epidemiologic Characteristics of Stroke in Sichuan Province, China - Liu, Qian; Xu, Xinyin; Fang, Jinghuan; Deng, Ying; He, Li (Frontiers in Neurology, 2020)
Previous studies have shown that there is a geographic variation in the prevalence of stroke, with a lower prevalence of stroke in Sichuan province. And a stroke transition was found during the period of economic development as well. However, as the center of Southwest China, with a greatly developed economy, whether the geographic variation remained with lower burden of stroke in Sichuan province is unknown. Therefore, in this study, we analyzed the secular stroke status in Sichuan province to help explore the potential reasons for geographic disparity. From a cross-sectional study conducted based on 8 national disease surveillance points (DSPs) in Sichuan Province in 2013 the epidemiologic data of stroke were collected. Data of risk factors were obtained from a cross-sectional study based on 12 national DSPs in Sichuan Province in 2013. The results showed that the standardized prevalence, incidence and mortality of stroke in Sichuan province were 338.6/100 000 people (95% CI, 267.8-409.4), 147.1/100 000 person-years (95% CI, 100.6-193.6), and 72.4/100 000 person-years (95% CI, 40.0-104.8), respectively, which were significantly lower than those determined from the contemporary data of China in 2013 . The analysis of the risk factors showed that the weights of contribution of the potential risk factors to stroke was in consistency with those published reports from other areas. In conclusion, the disparity of lower stroke burden in Sichuan than the average China remained, though with the great developments in Sichuan province over all those decades. In addition to traditional modifiable factors, we suggest that unknown or intrinsic differences such as genetic factors might play an important role in geographic disparity, which should be investigated in future studies.